2019
DOI: 10.1186/s13019-019-0952-5
|View full text |Cite
|
Sign up to set email alerts
|

Device closure of diverse layout of multi-hole secundum atrial septal defect: different techniques and long-term follow-up

Abstract: Background There are no unanimous reports on different layouts and classifications of multi-hole secundum atrial septal defects (MHASD) and subsequent standardized occlusion techniques. The MHASD can be isolated or cribriform with variable inter-defects distance. In this retrospective study, experience-based classification and two approaches-based occlusion results are presented. Methods We retrospectively collected and analyzed data of 150 MHASD patients from 1320 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…92% of patients had a complete occlusion of the defects at six and 12 months after the procedure [ 91 ]. Other investigators documented similar encouraging results [ 92 , 93 ]. The author’s personal experience with this device was limited but successful ( Figure 14 and Figure 15 ).…”
Section: Devices Currently In Usesupporting
confidence: 65%
See 1 more Smart Citation
“…92% of patients had a complete occlusion of the defects at six and 12 months after the procedure [ 91 ]. Other investigators documented similar encouraging results [ 92 , 93 ]. The author’s personal experience with this device was limited but successful ( Figure 14 and Figure 15 ).…”
Section: Devices Currently In Usesupporting
confidence: 65%
“… * Results of studies in children [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] and adults [ 61 , 64 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ] including FDA-approved US trial [ 80 ] and multi-institutional European studies [ 70 , 81 ] were reviewed and tabulated elsewhere [ 20 , 21 , 47 , 82 ]; # Similar results [ 92 , 93 ] were seen in other studies; ! Studies in children and adults [ 102 , 103 , 106 ] were similar; @ Similar results were reported in single institutional [ 107 , 108 ] and Canadian [ 109 ], European [ 110 , 111 ] and US [ 112 ] multi-institutional studies.…”
Section: Figurementioning
confidence: 99%
“…Of our 50 cases, four patients had RS immediately after surgery, with only one patient still having RS after the last follow-up, providing a closure rate of 98%. Farhaj et al reported on 150 multiple ASDs patients who underwent transcatheter closure, with 58 (38.7%) of the patients having immediate RS, and the complete closure rate was 80% at the 12-month follow-up ( 2 ). Even though RS was inevitable, Veldtman GR report that if the width of RS<3 mm, cardiac function recovered, murmur disappeared, the heart structure could be recovered, it is unnecessary for secondary closure ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The IDD was defined as the distance from the central defect (implanting hole) to the surrounding hole, which needed to be covered. The ASA met the following criteria ( 4 , 5 ): ( 1 ) the width of the aneurysmal base is more than 15 mm; ( 2 ) the excursion of ≥10 mm into the double atrium or the sum of bilateral excursion of >10 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation